2022
DOI: 10.4149/neo_2021_210818n1181
|View full text |Cite
|
Sign up to set email alerts
|

ASF1B enhances migration and invasion of lung cancers cell via regulating the P53-mediated epithelial-mesenchymal transformation (EMT) signaling pathway

Abstract: Lung cancer is one of the most common malignant tumors in the world. Anti-silencing function 1B (ASF1B) has been demonstrated to play crucial roles in various tumo rs. However, the function of ASF1B in lung cancer remains to be addressed. Quantitative real-time polymerase chain reaction (qRT-PCR) and western blot assays demonstrated that ASF1B expression was upregulated in human lung cancer tissues and cells. High expression of ASF1B in lung cancer patients was associated with tumor stage and lymph node metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Another co-expressed gene, NUSAP1 , is also recognized as an independent risk factor for HCC patient outcome, and regulates the expression of CDK4, CDK6, and cyclinD1, which participate in cell cycle progression [ 29 ]. Similar results have shown that ASF1B promotes aggressive features of invasion and metastasis in lung cancer cells via the p53 signaling pathway [ 30 ]. In addition, studies have confirmed that the positively correlated co-expression genes NUSAP1 , ASF1B , TPX2 , and SKA1 are invariably involved in immune cell infiltration in numerous cancers, and thus contribute to the regulation of the tumor immune microenvironment [ 29 , 31 33 ].…”
Section: Discussionsupporting
confidence: 78%
“…Another co-expressed gene, NUSAP1 , is also recognized as an independent risk factor for HCC patient outcome, and regulates the expression of CDK4, CDK6, and cyclinD1, which participate in cell cycle progression [ 29 ]. Similar results have shown that ASF1B promotes aggressive features of invasion and metastasis in lung cancer cells via the p53 signaling pathway [ 30 ]. In addition, studies have confirmed that the positively correlated co-expression genes NUSAP1 , ASF1B , TPX2 , and SKA1 are invariably involved in immune cell infiltration in numerous cancers, and thus contribute to the regulation of the tumor immune microenvironment [ 29 , 31 33 ].…”
Section: Discussionsupporting
confidence: 78%
“…Next, it was found that interference with ASF1B in Res186 cells could remarkably halt cell proliferation, metastasis and stimulate cell cycle arrest and apoptosis in LGG in our study. ASF1B could enhance the migratory as well as invasive capabilities of lung cancer cells via the modulation of p53-mediated epithelial-mesenchymal transformation signalling pathway [ 27 ]. MiR-214 inhibited the proliferative ability and promoted the apoptotic rate of myeloma cells by down-regulating ASF1B [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, one last additional pathway of interest is represented by p53, through its links with various drivers of EMT discussed in other chapters of this review. A first report described the importance of a chaperone protein of histone H3-H4, the anti-silencing function 1 (ASF1B), which promotes cell proliferation, migration, and invasion through the modulation of the p53mediated EMT signaling pathway (Wang et al, 2022). Secondly, Pustovalova et al shed light on the crosstalk between autophagy and this pathway (Pustovalova et al, 2021).…”
Section: Major Findings Relevant To Other Signaling Pathwaysmentioning
confidence: 99%